Modal analysis of concrete bridge decks subjected to free vibration: A research prospect / Norshariza Mohamad Bhkari, Azlan Abd. Rahman and Bederul Hisham Ahmad - Mohamad Bhkari, Norshariza; Abd. Rahman, Azlan; Ahmad, Bederul Hisham (2005)
This paper proposes a study on free vibration dynamic analysis for determining vibration parameters such as natural frequencies and mode shapes for two selected bridges in Johor. The vibration parameters for these bridges will be studied using finite element analysis software package ANSYS 6.0. These parameters will be measured by using the vibration dynamic measurement instruments that will be set-up in these bridges. Other data will be obtained from drawing provided by Public Works Department (PWD) that will be used in the analysis using ANSYS 6.0 program. The differences from these two methods will be compared. The modal updating will be used to make the analytical data closer to the field data by using FEM Tools program. The results of such analysis would be useful for early detection of deterioration in bridges and allows suitable maintenance solutions to be applied to the affected structures.